2020
DOI: 10.1126/sciadv.abd2712
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the PD-1 pathway

Abstract: Programmed Death-1 (PD-1; CD279) is an inhibitory receptor induced in activated T cells. PD-1 engagement by its ligands, PD-L1 and PD-L2, maintains peripheral tolerance but also compromises anti-tumor immunity. Blocking antibodies against PD-1 or its ligands have revolutionized cancer immunotherapy. However, only a fraction of patients develop durable antitumor responses. Clinical outcomes have reached a plateau without substantial advances by combinatorial approaches. Thus, great interest has recently emerged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
288
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 368 publications
(328 citation statements)
references
References 135 publications
1
288
1
4
Order By: Relevance
“…It is known that PD-1 interaction provides T-cell inhibitory signals. PD-1/PD-L engagement during TCR stimulation leads to tyrosine phosphorylation of the PD-1 cytoplasmic tail on high affinity sites for SH2 domain-containing phosphatase (SHP-2 and SHP-1), resulting in the dephosphorylation of proximal signaling molecules which decrease T cell proliferation and survival by attenuate PI3K and Akt pathways ( 31 , 34 ).…”
Section: Immune System In Gliomasmentioning
confidence: 99%
“…It is known that PD-1 interaction provides T-cell inhibitory signals. PD-1/PD-L engagement during TCR stimulation leads to tyrosine phosphorylation of the PD-1 cytoplasmic tail on high affinity sites for SH2 domain-containing phosphatase (SHP-2 and SHP-1), resulting in the dephosphorylation of proximal signaling molecules which decrease T cell proliferation and survival by attenuate PI3K and Akt pathways ( 31 , 34 ).…”
Section: Immune System In Gliomasmentioning
confidence: 99%
“…The ligands of PD-1 included PD-L1 and PD-L2 (12,13). The expression of PD-L2 on tumor cells is rare, and the role of PD-1/PD-L1 pathway in the regulation of anti-tumor immunity is more studied (14).…”
Section: Pd-1/pd-l1 Pathwaymentioning
confidence: 99%
“…Further studies revealed that the physiologic role of PD-1 is not related to cell death, but it is instead involved in regulation of immune responses, as demonstrated by the development of lupus-like autoimmune diseases in PD-1-deficient mice [12,13]. PD-1 belongs to the CD28/Cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) subfamily of the Immunoglobulin (Ig) superfamily [14] and it is a 50-55 kDa type I transmembrane glycoprotein [15]. PD-1 specifically binds the type I transmembrane proteins PD-L1 (B7-H1; CD274) [16,17] and PD-L2 (B7-DC; CD273) [18,19], both of which are B7 family members [20,21].…”
Section: The Pd-1 Immune Checkpointmentioning
confidence: 99%